Pengaruh Quality of Work Life terhadap Kepuasan kerja, Komitmen Organisasi, Turnover Intention dan Stres Kerja: Studi pada BMT Di Kabupaten Kudus - Wahibur Rokhman (Conference In Business, Accounting, And Management (CBAM), 2012)
This study investigates the effect of quality of work life on job satisfaction, organisational commitment, turnover intention and stress. This study uses a sample of 150 employees of Baitul Mal wa Tamwil (BMT) in Kudus Regency, Central Java, Indonesia. The results of Structural Equation Modeling (SEM) indicate that quality work life has positively significant impact on job satisfaction and organisational commitment. The findings also noted that, quality of work life negatifely affect on both turnover intention and stress. Overall the model supported that quality of work life has significant on job satisfaction, organisational commitment, turnover intention and stress. Implication, limitation and suggestion for future research are discussed.Keywords: Quality of work life, job satisfaction, organizational commitmen, turnover intention, dan stress kerja.